Management of a Complication of Percutaneous Gastrostomy in Children - Singh, Rashmi Roshan; Eaton, Simon; Cross, Kate M.; Curry, Joe I.; De Coppi, Paolo; Kiely, Edward M.; Roebuck, Derek J.; Pierro, Agostino (European Journal of Pediatric Surgery, 2013)
Aim “Buried bumper” is a complication of percutaneous gastrostomy related to the internal flange getting buried into the wall of the stomach. The aim of this study is to evaluate the management of this complication.Methods The surgical and interventional radiology database in our hospital from August 1999 to May 2011 was analyzed. There were 2,007 patients who underwent percutaneous gastrostomy insertion. Notes for patients with buried bumper were reviewed. A telephonic interview with the parents of these children was performed with focused assessment of the care of the gastrostomy tube before the episode of buried bumper. Continuous data are reported as median (range).Results Twenty children developed buried bumper after gastrostomy insertion. They had a primary diagnosis of neurological (n = 14), metabolic (n = 3), or endocrine (n = 3) disorders. The age at presentation was 5.7 years (2 to 18 years); 2.5 years (1 month to 5 years) after gastrostomy insertion. Ten children (50%) presented with symptoms related to buried bumper which included leakage around the gastrostomy (n = 4), pus, discharge or bleeding from the site (n = 5), stiffness on feeding (n = 3), and unable to push the flange (n = 1) (three children had more than one symptom). Ten children (50%) were asymptomatic and underwent routine change or removal of gastrostomy. In nine children, there was an attempt to remove the flange by interventional radiology but this was successful only in one. In the remaining 19 children, 4 had endoscopic removal while 15 children developed an inflammatory mass and required a laparotomy (n = 12) or laparoscopic-assisted excision (n = 3).Conclusion Buried bumper is a rare complication of percutaneous gastrostomy. Inadequate postoperative care without appropriate mobilization is a factor leading to this preventable complication. Endoscopic removal is possible, failing which laparoscopic surgery should be considered.
Keywords: buried gastrostomy; bumper; percutaneous gastrostomy; children